Peran Pancasila dalam Harmonisasi Hukum Internasional dan Hukum Nasional : Studi Kasus pada Perjanjian Ekstradisi - Ahmad Muhamad Musain Nasoha; Ashfiya Nur Atqiya; Omar Mochtar; Salma Keisa Azzahro Zain; Wahyu Sri Ningsih (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to analyze the role of Pancasila in the process of harmonizing international law and national law in Indonesia, with a focus on extradition agreements. As the state ideology and philosophical foundation of Indonesia, Pancasila provides principles that underpin the formation and implementation of national law. This study explores how Pancasila’s values, such as social justice and humanity, influence the policies and implementation of extradition agreements, as well as the challenges faced in aligning national law with international obligations. Using a qualitative approach and case studies, this research demonstrates that Pancasila functions as a moral and ethical guide that reinforces the integrity of Indonesian law in the global context. The findings are expected to provide insights into how the fundamental values of the state can strengthen the harmonization between national and international law and influence foreign policy and law enforcement in Indonesia.